IMAGINARY INACTIVITY AND THE SHARE BUTTON - Allaste, Airi-Alina; Tiidenberg, Katrin (AoIR Selected Papers of Internet Research, 2015)
Political participation is seen as a prerequisite for democratic governance (Lamprianou, 2013) but past decades have seen a steady decrease in electoral turnout and voting among younger generations in most European countries. This paper explores youth’s social media practices and the social imaginary of their political passivity. Using Estonian data from a 14-country European study Memory, Youth, Political Legacy And Civic Engagement (MyPLACE, 2011-1015) we thematically analysed in-depth interviews (60) in 2 contrasting sites and contextualized it with survey results from all participating countries. Instead of questioning how social media enables activism (Papacharissi & Oliveira, 2012, Coleman, 2013) or contrasting political commitment in internet based and physical-space activism (Morozov, 2011), our interest lies with understanding young people’s social media practices that could be considered a form (political) participation (liking and sharing political critique and parody, signing petitions), but which young people themselves do not recognize as such. Our central research interest lies with young people’s own social imaginary of youths’ political participation and social media practices.